IMPROVING STUDENTS’ ACHIEVEMENT IN WRITING RECOUNT TEXT THROUGH THINK PAIR SHARE - Hotria Manik; Elia Masa Ginting (Universitas Negeri Medan, 2013)
This study attempts to improve students’ writing achievement in recount text through Think-Pair-Share Strategy. This study was conducted by using classroom action research. The subject of the research was class VIII-1 SMPN 1 Pematangsiantar. The number of the students was 32 students, consisted of 5 males and twenty seven females. The research was conducted in two cycles and consisted of six meetings. The instruments for collecting data were writing tests as the quantitative data and diary notes, observation sheet, interview sheet and questionnaire sheet as qualitative data. Based on the writing score, students’ scores kept improving in every test. In analyzing the data, the mean of the students’ score for the first test as a pre-test was 57.84, for the second test as a post test I was 73.56, for the third test as a post test II was 77.56. Based on diary notes, observation sheet and questionnaire sheet, it was found that students were actively involved in writing process. The result of the research showed that Think-Pair-Share Strategy can improve students’ achievement in writing recount text. Keywords: Think Pair Share, Writing, Recount text, Action research